Characterization of microbial community assembly in parasitic plant systems and the influence of microorganisms on metabolite accumulation in parasitic plants: case study of Cistanche salsa and Kalidium foliatum - Feng, Zhan; Miao, Yujing; Sun, Xiao; Zheng, Yan; Luo, Guangming; Pei, Jin; Huang, Linfang (Frontiers in Microbiology, 2024)
Cistanche salsa (C.A.Mey.) G. Beck is a perennial holoparasitic herb belonging to the Cistanche genus, renowned for its kidney-tonifying and laxative properties. Despite its therapeutic potential, little is known about the endophyte communities inhabiting C. salsa and its host plants, and how these microorganisms may impact the production and accumulation of metabolites in C. salsa. To address this knowledge gap, we undertook a comprehensive metabolome analysis of wild C. salsa, as well as a microbiome analysis of both C. salsa and its host plant Kalidium foliatum (Pall.) Moq. The metabolomic analysis identified a total of 93 secondary metabolites and 398 primary metabolites in C. salsa, with the most significant differences observed in the flowers' metabolite composition. Furthermore, within various components of the entire parasitic plant system, the characteristics constraining microbial community compositions differ.Endophytic bacteria exhibit distinct community features between parasitic plants and their host plants, whereas differences in endophytic fungi are less apparent. Additionally, endophytic fungi demonstrate preferences for different microenvironments. Notably, our findings suggest that the presence of endophytes such as Bacteroidota, Proteobacteria, Ascomycota and Basidiomycota may influence the accumulation of 10 secondary metabolites in C. salsa, including salsaside, a metabolite specific to this plant species.